Analysis of Labor Productivity at the Pottery Craft Industry Center in Masbagik Timur Village, Masbagik District, East Lombok Regency - Ahmad Majdi; Akung Daeng; Tuti Handayani (West Science Social and Humanities Studies, 2025)
This study is entitled "Analysis of Labor Productivity in the Pottery Craft Industry Center in Masbagik Timur Village, Masbagik District, East Lombok Regency". The type of research used is descriptive research. The area and location of the research were conducted in Masbagik Timur Village. The types of data used are primary data and secondary data. Data collection techniques used are observation, interviews and literature studies. Determination of respondent samples using simple random sampling techniques. The analysis tool used to determine the amount of labor productivity is the productivity formula and productivity index. The results of the analysis (research) show that the value of labor productivity is greater than the value of the productivity index, which can be seen as follows: in the plate and ashtray business unit, the productivity index is 2.94 units/hour and the productivity is 3.75 units/hour. The business unit of jars, jugs, pots, and barrels, the productivity index is 0.47 units/hour and the productivity is 0.62 units/hour. The business unit of rice containers, kettles, and fruit containers has a productivity index of 0.94 units/hour and the productivity is 1.25 units/hour. The business unit of mortars and piggy banks has a productivity index of 1.92 units/hour and the productivity is 2.5 units/hour. The business unit of stoves has a productivity index of 1.44 units/hour and the productivity is 1.87 units/hour. The business unit of pestles has a productivity index of 3.84 units/hour and the productivity is 5 units/hour. So it can be seen that labor productivity in the pottery industry is large, because the productivity value is greater than the productivity index value.